Perbedaan Tingkat Pengetahuan dan Tingkat Pemahaman Porsi Makan Antara Instrumen Carbohydrate Counting Dengan Daftar Bahan Makanan Penukar Penyandang Diabetes Mellitus - Dwi Hananta Dewi; Muflihah Isnawati (JURNAL RISET GIZI, 2013)
Background of Study: Diabetes prevalence in Indonesia increases and occupies the forth position of theworld highest number of patients. There are increasing of number DM patient visiting nutrition clinic indr.R.Goeteng Tarunadibrata general Hospital Purbalingga, 36.36% in 2008 and 52.17% in 2009. Thediabetes mellitus patient with bad glucose rate in 2008 is 35% and increased up to 40% in 2009. Themethod of using in nutrition clinic of Purbalingga General Hospital is List of Substitutive Foodcomposition. There is a new instrument of nutrient counseling called Carbohydrate Counting.Objective: To find out the difference of knowledge and understanding level between the instrument ofcarbohydrate counting with the list of substitutive food composition of diabetes mellitus in the nutritionclinic of dr.R.Goeteng Tarunadibrata General Hospital Purbalingga.Method: This study design was quasi experimental with pre and post test design. The sample was takenby using purposive sampling in 2 months from November – December 2010.Result: The subject with carbohydrate counting instrument has medium knowledge 14.2% and highknowledge 85.8%, in other side on subject with the list of substitutive food composition instrument hashigh knowledge 100%. The subject with carbohydrate counting instrument hasn’t understand 57.1%and understand 42.9%, in other side on subject with the list of substitutive food composition instrumenthasn’t understand 42.9% and 57.1% understand.The statistic result of knowledge level p = 0.48 for pretestand p = 0.213 for post-test and the understanding level p = 0.615 for pre-test and p = 0.193 for posttest.Conclusion: There is no difference of knowledge and understanding level between the instruments ofcarbohydrate counting with the list of substitutive food composition of diabetes mellitus in the nutritionclinic of dr.R.Goeteng Tarunadibrata General Hospital Purbalingga.